Ligand-Gated Ion Channels as Targets for Treatment and Management of Cancers - Rao, Rohan; Shah, Sanjit; Bhattacharya, Debanjan; Toukam, Donatien Kamdem; Cáceres, Román; Pomeranz Krummel, Daniel A.; Sengupta, Soma (Frontiers in Physiology, 2022)
Ligand-gated ion channels are an ionotropic receptor subtype characterized by the binding of an extracellular ligand, followed by the transient passage of ions through a transmembrane pore. Ligand-gated ion channels are commonly subcategorized into three superfamilies: purinoreceptors, glutamate receptors, and Cys-loop receptors. This classification is based on the differing topographical morphology of the receptors, which in turn confers functional differences. Ligand-gated ion channels have a diverse spatial and temporal expression which implicate them in key cellular processes. Given that the transcellular electrochemical gradient is finely tuned in eukaryotic cells, any disruption in this homeostasis can contribute to aberrancies, including altering the activity of pro-tumorigenic molecular pathways, such as the MAPK/ERK, RAS, and mTOR pathways. Ligand-gated ion channels therefore, serve as a potential targetable system for cancer therapeutics. In this review, we analyze the role that each of the three ligand-gated ion channel superfamilies has concerning tumor proliferation and as a target for the treatment of cancer symptomatology.